Wymiany komponentów związków frazeologicznych w tekstach czeskich reklam - Cieciura, Piotr (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2009)
Autor zajmuje się w swoim artykule zagadnieniem innowacji frazeologicznej w tekstach czeskich reklam. Przedstawia cztery typy wymiany komponentów związków frazeologicznych: wymiany na element synonimiczny, wymiany na element o podobnych cechach formalnych, wymiany uwarunkowane charakterem reklamowanego produktu, swobodne wymiany elementów.

In his article the author presents the problem of phraseological innovation in texts of Czech advertisements. He presents four types of changes in the components of set phrases: changes into a synonymous element, changes into an element with similar formal properties, changes determined by the character of the advertised product and free changes of the elements.
Changes in the components of phrases in the texts of Czech advertising
Keywords: język czeski; czech language; reklama; advertising; czeskie frazeologizmy; Czech phrases; typy zmian komponentów frazeologicznych; types of changes in the components of phrases